Interferon alfa‐2a maintenance after salvage autologous stem cell transplantation in atypical mycosis fungoides with central nervous system involvement. (1st December 2019) - Doerschner, M.; Pekar‐Lukacs, A.; Messerli‐Odermatt, O.; Dommann‐Scherrer, C.; Rütti, M.; Müller, A.M.; Nair, G.; Kamarachev, J.; Kerl, K.; Beer, M.; Messerli, M.; Frauenknecht, K.; et al.
Summary: Mycosis fungoides (MF) is a primary cutaneous T‐cell lymphoma with unfavourable prognosis for patients with advanced stages of the disease. Refractory disease and advanced‐stage disease require systemic therapy. We report on a rare case of an atypical predominantly CD8 + folliculotropic MF, a subtype of MF with poorer prognosis, in a 59‐year‐old woman. She was initially diagnosed with MF restricted to the skin, of T3N0M0B0/stage IIB according to the current World Health Organization–European Organisation for Research and Treatment of Cancer classification. First‐line treatment with local percutaneous radiotherapy in combination with systemic interferon alfa‐2a resulted in complete remission. However, 21 months later the disease progressed to T3N0M1B0/stage IVB with development of cerebral manifestation and thus very poor prognosis. Allogeneic stem cell transplantation (SCT) was not a therapeutic option due to the lack of a suitable donor. We initiated methotrexate and cytarabine chemotherapy, followed by high‐dose chemotherapy with thiotepa and carmustine with autologous SCT. Despite rapid response and complete remission of the cerebral lesions, disease recurrence of the skin occurred soon after. Interestingly, readministration of interferon alfa‐2a as a maintenance treatment after the salvage autologous SCT resulted in a durable complete remission during the follow‐up period of currently 17 months after autologous SCT. What's already known about this topic? Mycosis fungoides is a primary cutaneous T‐cell lymphoma with unfavourable prognosis for the advanced stages of the disease. A refractory course of disease requires systemic therapy. What does this study add? We report on an unusual case of a patient with mycosis fungoides with cerebral involvement, in which a durable complete remission was achieved upon autologous stem cell therapy and interferon alfa‐2a maintenance therapy.